Dampak Energi Fosil Terhadap Perubahan Iklim Dan Solusi Berbasis Energi Hijau - Halim Tjiwidjaja; Rianti Salima (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2023)
This research aims to analyze the impact of fossil energy on climate change and explore green energy-based solutions. Research objects include greenhouse gas emissions produced by the use of fossil energy and the potential of renewable energy as an alternative. The research was carried out during 2023 using secondary data analysis methods from various case studies and scientific reports. research results show that the use of fossil energy contributes significantly to increasing global temperatures and extreme climate change. on the other hand, the application of green energy solutions, such as solar, wind, and bioenergy, can substantially reduce carbon emissions and increase environmental sustainability. Implementing policies that support the transition to green energy is urgently needed to overcome the climate crisis. This research provides recommendations for the development of renewable energy technology and increasing public awareness regarding the environmental impacts of fossil energy